Vegetative growth and thermal requirements of new papaya genotypes in the subtropical region of Argentina = Crescimento vegetativo e exigências térmicas de novos genótipos de mamoeiro na região subtropical da Argentina - Armella, Carina Mabel; Micheloud, Norma Guadalupe; Cariglio, Norberto Francisco; da Silva Vasconcellos, Marco Antonio (Sociedade Brasileira de Fruticultura (SBF), 2025)
The production of papaya in north-western Argentina is mainly based on the ‘Maradol Roja’ variety, with efforts underway to expand the available varietal options. The aim of this work was to evaluate the germination, vegetative growth, and phenology of different papaya genotypes introduced. Nine papaya genotypes were evaluated: seven from the Solo group and two from the Formosa group, with ‘Maradol Roja’ of the Formosa group used as the control. All genotypes showed germination rates above 70% at 30 days after sowing. However, differences in early seedling performance were observed. ‘RI511’ and ‘SSBs’ demonstrated superior seedling development at transplantation, while ‘GTHB’, ‘SSSy’, and ‘MR’ showed lower vigour. ‘Rubí INCAPER 511’ displayed the highest basal stem diameter, number of leaves per plant, and plant height at transplantation. Meanwhile, ‘Maradol Roja’, ‘Sunrise Solo Bs’ and ‘Rubí INCAPER 511’ were the first genotypes to reach flowering (within 64 to 75 days after transplantation). ‘Maradol Roja’ was also the most precocious to reach the first fruit set (100 days after transplantation) and harvesting. It had the smallest plant size and displayed the highest annual leaf appearances rate after flowering. Thermal accumulation from sowing to harvesting ranged from 4051-degree days for ‘Maradol Roja’ to 4540-degree days for ‘Sunrise Solo Aliança’. Papaya varieties from the Solo group with lower thermal requirements showed greater potential adaptability to the subtropical region of Jujuy Province, Argentina, as they are better able to complete the reproductive development and fruit ripening stages before the onset of low winter temperatures.